A pseudo random number generator based on chaos and irreducible polynomial - Özkaynak, Fatih (ISAST: International Society for the Advancement of Science and Technology, 2017)
Random numbers are critical topic in the information security. For example, private and public key cryptographic systems require random number in the encryption processes. But generation of random numbers are difficult task. Because it is not always possible to show that the desired security requirements have been achieved. This paper proposes a method generating pseudo random numbers. The unique aspect of proposed method is random numbers have been generated using strong cryptographic primitives. This property meets the desired security requirements. Another unique aspect of study is that the seed value of the generator has been determined using one dimensional chaotic circle map. This property aims to overcome the disadvantages of pseudo random number generators. Analysis and test results show that the proposed generator is suitable for practical applications.
10th International Conference on Chaotic Modeling and Simulation, CHAOS 2017 -- 30 May 2017 through 2 June 2017 -- Barcelona -- 151090
Keywords: Chaos; Circle map; Irreducible polynomials; Pseudo randomness; Random number generators